2013
DOI: 10.5539/jpl.v6n2p13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Redistricting Commissions on Electoral Competitiveness in U.S. House Elections, 2002-2010

Abstract: This research examines the various methods of electoral districting in the post-2000 Census years in order to determine the variation in competitiveness for subsequent elections to the U.S. House of Representatives. The evidence from this period suggests that "backup" and independent commissions resulted in more competitive districts, as measured by margin of victory and challenger win rate, after controlling for partisan and contextual factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…For instance, Grainger (2010, 545) finds evidence that “legislatively drawn districts have been, on average, less competitive than panel-drawn districts” in California since the 1960s. Also, Lindgren and Southwell (2013, 13) find that after controlling for partisan and contextual factors, “independent commissions resulted in more competitive districts, as measured by margin of victory and challenger win rate” in elections from 2002 to 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Grainger (2010, 545) finds evidence that “legislatively drawn districts have been, on average, less competitive than panel-drawn districts” in California since the 1960s. Also, Lindgren and Southwell (2013, 13) find that after controlling for partisan and contextual factors, “independent commissions resulted in more competitive districts, as measured by margin of victory and challenger win rate” in elections from 2002 to 2010.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have also suggested that independent commissions and courts should consider nonpartisan considerations that are intended to enhance electoral competition such as district compactness, responsiveness, and accountability (Butler and Cain 1992;Hirsch 2003). Other research has shown that districts shaped by commissions and courts (i.e., through nonlegislative redistricting) experience more competitive elections than those that undergo redistricting conducted by partisan state legislatures (Carson and Crespin 2004;Grose 2011;Cottrill 2012;Cottrill and Peretti 2013;Lindgren and Southwell 2013;Carson, Crespin, and Williamson 2014). No empirical relationship has been demonstrated between the partisanship of judges and electoral rewards for those judges' copartisans in congressional elections (at least from 2002 to 2010) (Cottrill and Peretti 2013), but some isolated , 1982-2012. nonpartisan plans commissioned by judges have seemed to reflect demonstrable copartisan bias (Kousser 1996).…”
Section: Judges and Legislators: Divergent Incentives For Electormentioning
confidence: 99%
“…Moreover, a few studies distinguish between partisan and bipartisan maps, and argue that partisan gerrymanders actually increase competition under certain circumstances (Gopoian and West 1984, Gelman and King 1994, Yoshinaka and Murphy 2011, Murphy and Yoshinaka 2009, Hood and McKee 2008. Recent scholarship has also focused on nonpartisan reforms, with independent commissions found to increase competitiveness (Carson andCrespin 2004, Lindgren andSouthwell 2013).…”
Section: B Competitivenessmentioning
confidence: 96%